GENDER PADA USAHA PENGOLAHAN IKAN KAYU DI PT. CELEBES MINAPRATAMA KOTA BITUNG - Christania Walukow; Srie J. Sondakh; Steelma V. Rantung; Jeannette F. Pangemanan; Swenekhe S. Durand; Florence V. Longdong (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2023)
Abstract The purpose of this study is to find out and find differences in gender work in each wood fish processing unit starting from the receipt of raw materials to exports and knowing the division of labor or the role of women and men (gender roles) in wood fish processing activities. Case studies are the basic method used in this study with data collection techniques using the purposive sampling method which is carried out with several considerations so that the data obtained will be more precise. The sample interviewed amounted to 10% of the population determined at each processing unit. Data collection is carried out through observation, interviews, questionnaires and documentation, both photo documentation and taking written documents at relevant agencies. Data collection is carried out through observation, interviews, questionnaires and documentation, both photo documentation and taking written documents at relevant agencies. The data obtained were then analyzed with an analysis of the Harvard Model developed by the Harvard Institute for International Development based on the Women in Development (WID) efficiency approach which is the earliest gender analysis and gender planning framework. All genders are employed in appropriate portions or corridors, namely the number of women is more in productive processing activities with a percentage of 61.42% because it is considered that these activities are easy to do and reach by female workers while men in reproductive processing activities with a percentage of 80.77% because these activities require extra energy but are assisted by machines to facilitate workers. The role of men is more in jobs that require extra energy, while women play an important role in light to moderate work with the characteristics of work that requires accuracy, patience and repetitiveness. Â Keywords: gender; processing; wooden fish Â  Abstrak Tujuan dari penelitian ini adalah mengetahui dan menemukan perbedaan pekerjaan gender pada setiap unit pengolahan ikan kayu mulai dari penerimaan bahan baku sampai ke ekspor serta mengetahui pembagian kerja atau peran perempuan dan laki-laki (peran gender) dalam kegiatan pengolahan ikan kayu. Studi kasus merupakan metode dasar yang digunakan dalam penelitian ini dengan teknik pengambilan data adalah dengan menggunakan metode purposive sampling yang diakukan dengan beberapa pertimbangan agar data yang diperoleh akan lebih tepat. Sampel yang diwawancarai berjumlah 10% dari populasi yang ditentukan pada setiap unit pengolahan. Pengumpulan data dilakukan melalui observasi, wawancara, kuisioner dan dokumentasi baik itu dokumentasi foto maupun pengambilan dokumen tertulis pada instansi terkait. Data yang diperoleh kemudian dianalis dengan analisis Model Harvard yang dikembangkan oleh Harvard Institute for International Development ini didasarkan pada pendekatan efisiensi Women In Development (WID) yang merupakan kerangka analisis gender dan perencanaan gender yang paling awal. Semua gender dipekerjakan pada porsi atau koridor yang sesuai yaitu jumlah perempuan lebih banyak pada kegiatan produktif pengolahan dengan persentase 61,42% karena dianggap kegiatan tersebut mudah dilakukan dan dijangkau oleh tenaga perempuan sedangkan laki-laki pada kegiatan reproduktif pengolahan dengan persentase 80,77% karena pada kegiatan tersebut membutuhkan tenaga ekstra tetapi dibantu dengan mesin untuk mempermudah pekerjan. Peranan laki-laki lebih banyak pada pekerjaan yang membutuhkan tenaga ekstra, sedangkan perempuan berperan penting pada pekerjaan ringan sampai sedang dengan karakteristik pekerjaan yang membutuhkan ketelitian, kesabaran dan berulang-ulang. Kata kunci: gender; pengolahan; ikan kayu